Facultades actualmente judiciales atribuibles al sistema notarial que no requieren potestad jurisdiccional - Martínez Salazar, Karina Alejandra (2025)
The congestion of the Ecuadorian judicial system and the structural difficulties in the execution of procedural acts such as service of summons motivated this research, which analyzes the possibility of transferring to the notarial system certain functions traditionally reserved for judges. The general objective was to determine the attributions that, by their nature, do not require the exercise of judicial authority and may therefore be assigned to notaries. A qualitative methodology with a descriptive and analytical approach was applied, combining the documentary study of legal norms, specialized doctrine, comparative law, and semi-structured interviews with notaries, judges, and lawyers. The analysis revealed that notaries, as public faith officials, can legitimately intervene in acts of voluntary jurisdiction, such as acceptance and partition of inheritances, consensual divorces, authorizations for minors to travel abroad, and, innovatively, in the execution of summonses under certain conditions. Among the relevant findings, it was identified that judicial service of summons, although historically considered a substantial act of jurisdiction, faces serious practical efficiency problems that affect procedural celerity. In this context, it is concluded that summonses can and should be carried out by notaries, optionally for users who request it, with fees regulated by the Judiciary Council and through technical, legal, and technological protocols that safeguard the right to defense. The study proposes specific legal reforms and opens new lines of research on strengthening the notarial role in supporting the administration of justice, consistent with comparative models and the development of emerging legal technologies.